Impact of temperature stress on secondary metabolite profile and phytotoxicity of Amaranthus cruentus L. leaf extracts - Maria Elizabeth CAWOOD; Ingrid ALLEMANN; James ALLEMANN (Acta Agriculturae Slovenica)
In this study Amaranthus cruentus plants were grown under controlled optimal conditions (28/21 °C) for three months and then subjected to cold (14/7 °C) and hot (33/40 °C) temperatures. We investigated the influence of these temperature regimes on the metabolite profile of the leaves through analyses of data by TLC, HPLC and GC-MS spectrometry. The phytotoxic potential of a methanol-water (MW) and dichloromethane (DCM) extract from the aerial parts were examined through in vitro screening of germination and growth of lettuce and pepper. The optimal extracts displayed the highest diversity of secondary metabolites, and the highest total phenolics and flavonoids content. Through TLC and HPLC analysis the significantly lower phenolic content in the hot temperature treated samples was confirmed. A wide range of metabolites were detected in the DCM extracts through GC-MS analyses. The phytotoxicity of both the MW and DCM extracts were demonstrated, as germination and growth of pepper and lettuce were significantly inhibited, indicating the presence of more than one allelochemical compound which may affect the allelopathic activity of A. cruentus during changes in environmental temperatures.